Assessment of noise in the airplane cabin environment. (November 2018) - Zevitas, Christopher; Spengler, John; Jones, Byron; McNeely, Eileen; Coull, Brent; Cao, Xiaodong; Loo, Sin; Hard, Anna-Kate; Allen, Joseph
Abstract Objective To measure sound levels in the aircraft cabin during different phases of flight. Methods Sound level was measured on 200 flights, representing six aircraft groups using continuous monitors. A linear mixed-effects model with random intercept was used to test for significant differences in mean sound level by aircraft model and across each flight phase as well as by flight phase, airplane type, measurement location and proximity to engine noise. Results Mean sound levels across all flight phases and aircraft groups ranged from 37.6 to >110 dB(A) with a median of 83.5 dB(A). Significant differences in noise levels were also observed based on proximity to the engines and between aircraft with fuselage- and wing mounted engines. Nine flights (4.5%) exceeded the recommended 8-h TWA exposure limit of 85 dB(A) by the NIOSH and ACGIH approach, three flights (1.5%) exceeded the 8-h TWA action level of 85 dB(A) by the OSHA approach, and none of the flights exceeded the 8-h TWA action level of 90 dB(A) by the OSHA PEL approach. Conclusions Additional characterization studies, including personal noise dosimetry, are necessary to document accurate occupational exposures in the aircraft cabin environment and identify appropriate response actions. FAA should consider applying the more health-protective NIOSH/ACGIH occupational noise recommendations to the aircraft cabin environment.